ANALISIS RANTAI PASOKAN TANDAN BUAH SEGAR KELAPA SAWIT DI PTPN V SEI PAGAR KABUPATEN KAMPAR - Febro Sarjana Purba; Novia Dewi; Evy Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Palm oil (Elais guineensis Jacq.) Is an oil-producing plantation which is an important component for people's economy, among others in the absorption of manpower, and as a source of foreign exchange. This Study were aimed to Know the supply chain performance of FFB in palm oil mill Factory PTPN V Sei Pagar. The study started from December 2016 until March 2017.  The respondents of this study were taken by accidental sampling. Data analysis using qualitative and quantitative analysis The results showed, in the upstream supply chain, the supply of TBS raw materials came from 5 gardens, namely: core garden, plasma, KKPA, other gardens and third parties. The amount of FFB supply of each garden is 21,937,600 kg, 35,995,550 kg, 5,287,110 kg, 2,313,680 kg, and 92,819,310 kg. In the internal management is known, the number of factory working hours amounted to 5.296 hours / year with CPO production of 29,524,610 kg and kernel production of 7,986,410 kg. In the downstream supply chain is known, the processed palm fresh fruit bunches of CPO are sold to 7 different companies through one transporter agent, while the kernel distribution is done through 3 transporter agents with the same purpose.Keywords: supply, chain, Oil Palm, kernel.